Aerobic exercise training and arterial changes in African Americans versus Caucasians - Ranadive, S. M.; Yan, H.; Lane, A. D.; Kappus, R. M.; Cook, M. D.; Sun, P.; Harvey, I.; Ploutz-Synder, R.; Woods, J. A.; Wilund, K. R.; Fernhall, B. (Medicine & Science in Sports & Exercise, 2016)
African Americans (AA) have increased carotid artery intima-media thickness and decreased vascular function compared with their Caucasian (CA) peers. Aerobic exercise prevents and potentially reverses arterial dysfunction.